ARID1A deficiency in EBV-positive gastric cancer is partially regulated by EBV-encoded miRNAs, but not by DNA promotor hypermethylation. (16th November 2020) - Kase, Koji; Saito, Motonobu; Nakajima, Shotaro; Takayanagi, Daisuke; Saito, Katsuharu; Yamada, Leo; Ashizawa, Mai; Nakano, Hiroshi; Hanayama, Hiroyuki; Onozawa, Hisashi; Okayama, Hirokazu; Endo, Hisahito; et al.
Abstract: AT-rich interactive domain 1A ( ARID1A ), which is a tumor suppressor gene, is frequently mutated in Epstein-Barr virus-positive gastric cancer [EBV (+) GC]. While most ARID1A mutations in GC are truncating mutations, leading to loss of ARID1A protein expression, epigenetic modifications appear to contribute to ARID1A deficiency in EBV (+) GC harboring wild-type ARID1A . Based on the significant role of epigenetic modifications in EBV (+) GC that contributes to ARID1A deficiency, the methylation status of ARID1A was evaluated in EBV-infected cells and GC patients using a publicly available microarray and the Cancer Genome Atlas (TCGA) database. EBV-encoded miRNAs that potentially target ARID1A were identified as an additional epigenetic modulator by computational prediction. In vitro experiments were conducted to evaluate how EBV-encoded miRNAs affected ARID1A mRNA and protein levels. In clinical GC samples, the expression of predicted miRNAs and ARID1A and the mutation status of ARID1A was evaluated. As results, ARID1A was not hypermethylated in EBV (+) GC samples or EBV-infected GC cells. EBV infection did not alter ARID1A mRNA levels, suggesting that ARID1A protein deficiency was caused by post-transcriptional gene silencing in ARID1A -WT EBV (+) GC. Overexpression of miR-BART11-3p and miR-BART12, which were identified as miRNAs that potentially bind ARID1A, suppressed ARID1A protein expression in MKN7 and NCI-N87 cells. Highly expressed miR-BART11-3p and miR-BART12 were correlated with decreased ARID1A levels in GC tumors which did not harbor ARID1A mutations. The present findings revealed that ARID1A expression was epigenetically regulated by miR-BART11-3p and miR-BART12 in EBV (+) GC. Abstract : EBV-encoded miRNAs were specifically expressed in EBV-positive gastric cancer, and ARID1A expression was epigenetically regulated by miR-BART11-3p and miR-BART12, but not by DNA promotor hypermethylation, in EBV-positive gastric cancer.